PERKEMBANGAN KAJIAN TEORITIS TAFSIR KONTEMPORER DI TIMUR TENGAH - Isnan Ansory (Karimiyah: Journal of Islamic Literature and Muslim Society, 2023)
The theoretical study of the interpretation of the Qur'an in the contemporary era has experienced significant developments, especially in the Middle East region. Various methodologies and new systematics of the interpretation of the Qur'an, quite a lot have sprung up. This is marked by the proliferation of various interpretations of the Qur'anic literature with various interpretations and also the systematic writing of new interpretations that have never been done before. From a search of various literatures about contemporary interpretation, especially for the Middle East region, it is concluded at least 6 theories regarding the study of interpretation of the Qur'an. Namely, the study of the theory of the sources of the interpretation of the Qur'an, the study of the method of interpretation of the Qur'an, the study of the theory of the style of the interpretation of the Qur'an, the philological study of classical commentary texts, the study of the criticism of the interpretation and the study of on the aqwal tafsiriyyah of the scholars.